2008
DOI: 10.1007/s00441-007-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cells cultured from omentum express pluripotent markers, produce high amounts of VEGF, and engraft to injured sites

Abstract: When rat omentum becomes activated by intraperitoneal injection of inert polydextran particles, these particles are rapidly surrounded by cells that express markers of adult stem cells (SDF-1alpha, CXCR4, WT-1) and of embryonic pluripotent cells (Oct-4, Nanog, SSEA-1). We have cultured such cells, because they may offer a convenient source of adult stem cells, and have found that they retain stem cell markers and produce high levels of vascular endothelial growth factor for up to ten passages. After systemic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 41 publications
2
48
0
1
Order By: Relevance
“…These findings suggest that the omentum plays an important role in bringing about growth and regeneration of the injured liver. The amount of liver growth induced by the omentum was proportional to the degree of omental activation, consistent with our previous observations that the concentration of growth factors and the number of progenitor cells in the omentum increase with increased activation [7,8] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings suggest that the omentum plays an important role in bringing about growth and regeneration of the injured liver. The amount of liver growth induced by the omentum was proportional to the degree of omental activation, consistent with our previous observations that the concentration of growth factors and the number of progenitor cells in the omentum increase with increased activation [7,8] .…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies we investigated this process and found that these properties can be enhanced by physically expanding the omentum with foreign particles. Under such conditions, the expanded omentum becomes rich in growth and angiogenic factors, and has abundant progenitor cells [7,8] . In a separate study we used this approach to generate new β-cells from the diabetic pancreas [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists isolated, cultured and characterised these omentum fat derived cells from rat and asserted that these cells exhibited multilineage properties of stem cells which are capable of finding its use in repair and regenerative applications (Tholpady et al 2003;Singh et al 2008). Subsequently, there has been a very scanty citation of similar research with human omentum fat derived stem cells (Baglioni et al 2009;Toyoda et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…11 These healing properties of the omentum have been attributed to its high content of progenitor cells as well as growth and angiogenic factors. 12,13 Although adult stem cells have shown promise in treating AKI, [14][15][16][17][18] whether they could alleviate CKD has not been fully explored. One technical problem encountered in experimental investigation of this issue is the fact that adult stem cells do not survive in the body for more than a few days after injection [19][20][21] ; therefore, stem cells will have to be injected every few days for several weeks to see an observable effect.…”
mentioning
confidence: 99%